Our unique clinical pathway for congestive heart failure cases required admission achieved a dramatic reduction of their hospitalization period and a significant reduction of readmission with heart fa. (25th November 2020) - Takaishi, A; Kisinoue, T; Mori, H; Yoshino, T; Yamaji, T; Yasuhara, K; Tanimoto, M; Kagawa, K; Onishi, N; Imai, M; Ueeda, M
Abstract: Background: In recent years, the number of elderly congestive heart failure (CHF) cases has been increasing in Japan with the aging of the population. This tendency is particularly remarkable in rural areas where our facilities are located. After admission with CHF, the hospitalization period (PE) was prolonged due to various complications unique to the elderly, and re-exacerbation of CHF occurred shortly after discharge. Approximately 30% of them were readmitted within one year. From August 2015, for shortening of PE and reduction of CHF readmission through the efficiency of CHF treatment and comprehensive patient education, we had introduced a unique clinical pathway (PATH) that provided the immediate use of Tolvaptan and comprehensive education by multi-disciplinary staff after admission. Purpose: In this study, we verified whether the improvement of clinical prognosis were achieved by introduction of PATH. Methods: Between April 2014 and July 2019, 635 CHF cases (764 admissions) ware enrolled. We divided them to two groups, N-group before introducing PATH (198 cases, 262 admissions) and P-group applied PATH (437 cases, 502 admission). Between both groups, we compared the various acute care situation, PE and readmission rate with CHF within 1 year after discharge. Results: There were no differences between P and N-group in mean age, distribution of underlying illness or daily activity level before admission. There ware not also differences about left ventricle function by echocardiography and various blood test data at admission. The enforcement rate of continuous infusion and the rate of urinary catheter placement were significantly lower in the P-group (71 vs 88%; p<0.0001, 52 vs 63%; p<0.01, respectively). And their enforcement duration was significantly shorter in P-group (4.6±5.3 vs 10.5±9.6 days; p<0.0001, 6.3±7.9 vs 12.8±13.1 days; p<0.0001 respectively). The enforcement rate of cardiac rehabilitation was significantly higher in group P (94 vs 84%; p<0.0001), and the starting time of rehabilitation was significantly earlier (2.9±1.5 vs 6.3±4.8th illness day; p<0.0001). As a result, the average HP was significantly shorter in group P (16.5±13.4 vs 28.6±24.1 days, p<0.0001). The readmission rate with CHF within one year after discharge was significantly lower in group P (23 vs 36%; p<0.001). Conclusion: By the introduction of our original clinical pathway for congestive heart failure, the efficiency of medical care was achieved and the mean hospitalization period was widely shortened. In addition, by the through comprehensive patient education by multi-disciplinary staff involved in the pathway, the self-restraint life style after discharge seemed to be maintained and the readmission with worsening of heart failure was significantly suppressed. Funding Acknowledgement: Type of funding source: None